The impact on leadership style towards employee motivation among employees in Tenaga Nasional Berhad, Johor Bahru, Johor / Zur Aina Zulazli - Zulazli, Zur Aina (Faculty of Business and Management, 2018)
This paper examines on the employee’s motivation and the relationship with transformational leadership style and transactional leadership style. The study highlighted and defines on the basic concepts of transformational and transactional leadership style that may affected on the employee’s motivation. The total population of this study consist of 290 employees. The total sample size of this survey was collect 165 questionnaires. The data that been collected later was process using a Sastical Package for Social Science version 20. The data that been collected are also been analyzed using a Descriptive, Pearson Correlation and Multiple regression. Thus, the result that been study reveal that there is a positive relationship between all the independent variables which is transformational leadership style and transactional leadership style have positive relationship towards employee motivation. Despite that, there is also many other factor that are contributed to the employee’s motivation which are not included and mentioned in this study. The sample study is only limited to the employees that are working in Tenaga Nasional Berhad, Johor Bahru.